Cyclic Peptides in Pipeline: What Future for These Great Molecules? - Lia Costa; Emília Sousa; Carla Fernandes (MDPI AG, 2023)
Cyclic peptides are molecules that are already used as drugs in therapies approved for various pharmacological activities, for example, as antibiotics, antifungals, anticancer, and immunosuppressants. Interest in these molecules has been growing due to the improved pharmacokinetic and pharmacodynamic properties of the cyclic structure over linear peptides and by the evolution of chemical synthesis, computational, and in vitro methods. To date, 53 cyclic peptides have been approved by different regulatory authorities, and many others are in clinical trials for a wide diversity of conditions. In this review, the potential of cyclic peptides is presented, and general aspects of their synthesis and development are discussed. Furthermore, an overview of already approved cyclic peptides is also given, and the cyclic peptides in clinical trials are summarized.